2011
DOI: 10.1007/s11195-011-9201-0
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of Sexual Relationships Among People with Learning Disabilities: Family and Professional Caregivers’ Views in Mexico

Abstract: The attitudes towards sexual relationships among persons with learning disabilities (PLD) of parents of children without disabilities were compared with the attitudes of family caregivers (parents of PLD) and with the attitude of professional caregivers. The importance of different situational factors that may alter acceptability judgments (i.e., gender, etiology of the disability, person's present level of autonomy, use of contraceptive devices, and partner's age and possible handicap) with regards to the sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 18 publications
(30 reference statements)
0
34
0
3
Order By: Relevance
“…By using an IIT approach, it is possible to identify the use of cognitively ruled behaviour underlying judgment formation in many complex psychological domains [32], such as love [33], sexuality [34,35,36], medical concerns [37], interpersonal relationships [29], pleasure-related visual and auditory stimuli [38,31], health [39], bioethics [40], ID and love [41,24]. Here, we will employ the IIT in the context of school inclusion to explore how people cognitively use or combine individual, situational, and/or contextual factors to elaborate success judgments about regular school inclusion and ID.…”
mentioning
confidence: 99%
“…By using an IIT approach, it is possible to identify the use of cognitively ruled behaviour underlying judgment formation in many complex psychological domains [32], such as love [33], sexuality [34,35,36], medical concerns [37], interpersonal relationships [29], pleasure-related visual and auditory stimuli [38,31], health [39], bioethics [40], ID and love [41,24]. Here, we will employ the IIT in the context of school inclusion to explore how people cognitively use or combine individual, situational, and/or contextual factors to elaborate success judgments about regular school inclusion and ID.…”
mentioning
confidence: 99%
“…This hypothesis was partially corroborated by studies with pedagogues working with persons with an intellectual disability and Pedagogy students [23, 27], however other studies with various specialists proved otherwise [18]. Morales et al [28] showed in studies with parents and guardians that acceptance of sexual relations depends on various factors, among others: sex, level of autonomy, contraception methods used and the age of partners. A significant differentiating factor in determining attitudes towards sexual relationships of individuals with intellectual disability is the issue of them being able to consciously give consent [29].…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that specialists give positive scores to sexuality of individuals with an intellectual disability and treat it as normal and natural, emphasizing the need of sexual education, but also display ambivalence or negative attitudes towards procreation of such individuals. Morales et al [28] observe that “overall, attitudes towards the sexuality of people with an intellectual disability are moderately positive, more liberal now than they were 20 years ago (…) respondents’ main concerns, presently, are more centered on the consequences of the sexual relationships than on the relationships per se”. One of such consequences is parenthood.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand the sexual needs of these women are often ignored, curtailed or actively denied by professionals, their primary caregivers or parents as well as the general community (Morales, Lopez & Mullet, 2011;Szollos & McCabe, 1998). On the other hand, over-protective attitudes toward women with intellectual disabilities typically stem from the desire to protect them from unpleasant experiences, although it is these very experiences which help them grow (Deeley, 2002).…”
Section: Introductionmentioning
confidence: 99%